بۆچوونی گەنجان سەبارەت بە ڕۆڵی بەرنامە تەلەڤزیۆنییەکان لە ناساندنی بێکارییدا - حسن, پ. د. هێمن مجيد; قادر, سەربەست حسين (Sulaimani Journal for Humanities, 2023)
This research wants to discuss the relationship between youth attitude and television programs in the Kurdistan Region. The main reason for this research is the uncertainty of youth attitude about the role of televisions in the Kurdistan Region to discuss and define unemployment within their programs. in order to reach the level of attention of Kurdish televisions to introduce and discuss unemployment from the perspective of young people. The most main issues of the research are: to what extent the Kurdish televisions Have devoted space to introducing and exposing unemployment? To what extent Kurdish television stations in the Kurdistan Region have been able to explain the viraity dimensions of unemployment in their programs? Likewise, The most obvious porpuses of the study are: to reach the level of space Kurdish televisions in the Kurdistan Region have devoted to interduce unemployment in their programs. Also, to knowing the amount of explanation that Kurdish televisions have done to interduce viritey dimensions of with in their programs in the Kurdistan Region. The study is (descriptive) resesearch, relies on (survey and interview) methods. The research population and sample consists of young people in the Kurdistan Region, specifically the center of the two provinces of Sulaimani and Erbil. The research consists of three parts: (methodology, information and practical part). The most important findings of the researcher are that there is no continuous program on unemployment and unemployment promotion on Kurdistan Regional Government televisions. Kurdish television stations have largely neglected to explain the meaning and consequences of unemployment to their viewers. According to the youth, Kurdish television stations in the region have not devoted enough space to introduce unemployment in their programs. The researcher also made some suggestions, the most important of which are that Kurdish televisions in the Kurdistan Region have continuous programs related to unemployment and similar issues, the relevant parties and televisions to coordinate with researchers who works on unemployment issues to work on it، base on infotmstion and data.